Automatic Safe Security System Using Pin Code And Fingerprint Based On Microcontroller With Telegram Notification - Chanifudin, Achmad Yahya; Ayuni, Shazana Dhiya; Falah, Agus Hayatal; Sulistiyowati, Indah (Universitas Nurul Jadid, 2025)
The primary purpose of a security system is to protect valuable and important items. A safe is a medium for storing valuables, adjusted to the size of the safe compartment. Therefore, a proper security system is needed to ensure the owner does not worry about the loss or theft of the contents. This security system is adapted to the current era of advanced and modern technology. The sensors and microcontroller used include the NodeMCU ESP8266, fingerprint sensor, keypad, and LED indicator lights. Telegram notifications or alerts via the application can be received through an internet connection. This security system is implemented to secure the safe and can be accessed via an Android smartphone with the Telegram app installed. It enables the owner to receive access notifications indicating whether an attempt was successful or failed. This research was conducted using an experimental method by building a device to enhance the safety of the safe, providing peace of mind about the stored items. The experiment was carried out at a residence located in Bendosari Village, Ngantru District, Tulungagung Regency. Based on the results, it can be concluded that the development of an automatic safe using a pin code and fingerprint based on a microcontroller with Telegram notifications has successfully met the research objectives. All sensors and components within the safe function properly, ensuring the protection of valuables inside and offering peace of mind to the owner.